2011
DOI: 10.1111/j.1744-697x.2011.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground plant mass and mass available to grazing goats in a mountainous shrubland in subtropical China

Abstract: Vegetation in the northwestern mountainous region of Guangdong Province, China is a mosaic of forests and shrubs. Shrubs in this area are evergreen with heights <2.5 m and have been left unused for at least 50 years. Recently, light grazing by a local breed of goats was started in a mountainous region near Lechang City under local government guidance. We conducted a survey over 4 years to estimate plant mass as a feed resource for goats in a sharply undulating mountainous shrubland. Two permanent plots (50 × 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…NOR was frequently found at concentrations as high as 66.7 μg/kg in the irrigated soils. NOR is one of the most frequently detected antibiotics in various environmental media including water, soil, and plants, 17,38 which could be related to its extensive medical and veterinary use. It may also come from animal manure, 39 which was commonly applied in these areas.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…NOR was frequently found at concentrations as high as 66.7 μg/kg in the irrigated soils. NOR is one of the most frequently detected antibiotics in various environmental media including water, soil, and plants, 17,38 which could be related to its extensive medical and veterinary use. It may also come from animal manure, 39 which was commonly applied in these areas.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…However, limited information is available on the long‐term spatiotemporal variation in aboveground biomass in pastures. Although Jones et al (1995) and Yiruhan et al (2001) reported temporal variation in aboveground biomass in sown pastures under cattle grazing over a 21‐year period, they did not quantitatively show the effects of climate and management in the form of a model for aboveground biomass. Although Vázquez‐de‐Aldana et al (2008) conducted 20‐year monitoring of aboveground biomass in a native pasture grazed mainly by cattle and developed models to relate aboveground biomass to climatic variables, they focused only on interannual variation without incorporating seasonal variation into the models.…”
Section: Introductionmentioning
confidence: 98%
“…18 Annual worldwide antibiotic usage is estimated at 100 000− 200 000 tons, and annual consumption in China of more than 25 000 tons. 19 A quantity of antibiotics are excreted in urine and then released into the aquatic environment via a sewage treatment plants (STP) due to limited removal efficiencies [e.g., moxifloxacin (MOXI, 40%), gatifloxacin (GATI, 43%), ofloxacin (OFL, 33−66%), lomefloxacin (LOME, 21−72%), 20 trimethoprim (TMP, 3%), 21 and oxytetracycline (OTC, 38%) 22 ]. Some antibiotics, such as sulfamethoxazole (SMX), show increased concentrations in STP effluent.…”
Section: ■ Introductionmentioning
confidence: 99%